Customer analysis in the portuguese toy market - a customer relationship management project for science4you: Report: A – Strategic Analysis and Recommendations on CRM for the Frequently Last Say Adult Segment - Pedroso, Madalena de Noronha Demony Consiglieri (2020)
The toymarket has not remained static overthe years, having suffered big transformations and adapting to the evermore digital world.ThisWork Project’s relevanceis supported by the way it combines the current digital trends, the organizations’ shift from product to customer-centricity,and the importance of family dynamics in the Toy Industry.An extensive approach was developed, including a bibliographic review and a primary research, allowing a behavioral-based analysis ofthe company ́s current and potential customers. The obtained insights allowed to pursuethe objective of delivering customer relationship managementstrategic recommendations, guiding Science4youto better allocatemarketing and communication resources.